Bridging Theory and Practice: The Effectiveness of the Hybrid Contextual-Project Based Learning Model in Islamic Economics Courses - Kuswanto Kuswanto; Abderrazak Belabes; Muhammad Arif Liputo (Jurnal Pendidikan Progresif, 2026)
Sharia Economics education faces significant challenges due to the diverse educational backgrounds of students, the majority of whom are not graduates of Islamic boarding schools (pesantren). This makes the technical terminology of muamalah a significant linguistic barrier. Furthermore, conventional approaches often produce only a superficial understanding (illusion of competence) without adequate depth of material. This study evaluates the implementation of a Hybrid Learning model that integrates Contextual Teaching and Learning (CTL) and Project-Based Learning (PjBL) to align theory with practical realities and improve student learning outcomes. Utilizing a quasi-experimental nonequivalent control group design, this study involved 65 students divided into one experimental class and two control classes. The experimental group engaged with the Hybrid Contextual-Project-Based Learning model, whereas the control group adhered to conventional teaching methods. Learning outcomes were measured using standardized tests and analyzed using One-Way ANOVA, followed by Tukey's HSD post hoc testing. The analysis revealed a statistically significant disparity in learning outcomes. The experimental class achieved a superior average score of 68.43, outperforming the control classes, which averaged between 55 and 57 by more than 10 points. Furthermore, the consistently low performance across both control groups highlights the limitations of traditional methods in fostering deep comprehension. The Hybrid Contextual-Project-Based Learning model demonstrates significant effectiveness in boosting academic competence. By shifting the focus from rote memorization to practical mastery, this model mitigates the "illusion of competence" often present in traditional learning. Consequently, this approach is recommended as an adaptive instructional strategy for cultivating highly capable graduates in Islamic economics. Keywords: hybrid learning, contextual approach, project-based learning, islamic economics education, competency gap.